1991
DOI: 10.1111/j.1460-9568.1991.tb00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Specificity in the Development of Vertical Connections in Cat Striate Cortex

Abstract: The main efferent axons of pyramidal cells in layer 2/3 in the adult cat striate cortex make collateral connections specifically within layer 2/3 and layer 5 and avoid the intervening layer 4. Intracellular dye injections in vitro were used to determine how, during early postnatal development, this precise pattern of laminar connections was achieved. These investigations revealed that the pattern of collateral outgrowth was specific from the very earliest time that axons began sprouting collaterals. During the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 39 publications
3
36
1
Order By: Relevance
“…The formation of collateral branches was highest on membrane substrates from the target layers and not necessarily on membrane substrates which contained the highest concentration of growth promoters. In vivo, collaterals emerge in the target layers from the main efferent axon after it has grown out of the cortex (21). Sprouting of collateral branches from the primary axon shaft can also occur during the formation of cortical projections to distant targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of collateral branches was highest on membrane substrates from the target layers and not necessarily on membrane substrates which contained the highest concentration of growth promoters. In vivo, collaterals emerge in the target layers from the main efferent axon after it has grown out of the cortex (21). Sprouting of collateral branches from the primary axon shaft can also occur during the formation of cortical projections to distant targets.…”
Section: Discussionmentioning
confidence: 99%
“…In the developing cat visual cortex in vivo, it has been reported that axonal branches are almost never observed in inappropriate layers (21). There are several possibilities to explain why the branching specificity in the developing rat cortex in vitro is not as sharp as in cat cortex in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Layer 2/3 Pyramidal Neurons-The development of layer 2/3 pyramidal neurons has previously been described in cats, ferrets, and monkeys (Katz, 1991;Callaway, 1998b;Borrell and Callaway, 2002). Layer 2/3 pyramidal neurons in these studies show a high degree of specificity at all time points, with axons arborizing within layer 2/3 and layer 5 and avoiding layer 4 and layer 6.…”
Section: Development Of Axonal Laminar Specificitymentioning
confidence: 94%
“…An inhibitory mechanism has been suggested for local cortical circuit formation by the observation that collaterals of developing layer 2/3 neurons emerge only in layers 2/3 and 5 from the outset but never appear in layer 4 (Katz, 1991). Likewise, it has also been shown that layer 6 axons bypass layer 5 and arborize specifically in layer 4 in vivo and in vitro (Callaway and Lieber, 1996;Dantzker and Callaway, 1998).…”
Section: Possible Mechanisms For Lamina-specific Branch Formationmentioning
confidence: 99%